Legal Protection of Children in Kazakhstan: Problems and Challenges - Gakku Rakhimova; Zhanna Khamzina; Nessibeli Kalkayeva; Yermek Buribayev; Zhanel Sailibayeva (Universitas Negeri Semarang, 2024)
Since Kazakhstan's independence in 1991, the nation's child protection legal framework has evolved through three distinct phases: inception, establishment, and initial development. This evolutionary journey has yielded significant progress in multiple facets of child protection, including the refinement of legislative aims; principles; and the conceptual and substantive aspects of child welfare. Notably, this progression encompasses enhanced measures in criminal, civil, and administrative justice for child protection, as well as improved mechanisms for the monitoring and execution of these laws. Central to this advancement is the embodiment of the United Nations Convention on the Rights of the Child's guiding principles: prioritizing the child's best interests, ensuring non-discrimination, respecting the child's opinions, and safeguarding rights fundamental to the child's survival and growth. These principles are now integral to Kazakhstan's pertinent legal instruments. Despite these strides, challenges persist in the realm of child legal protection in Kazakhstan.